Design of controllable degradable epoxy resin: High performance and feasible upcycling. (1st February 2022) - Feng, Haoyang; Jin, Dandan; Wang, Shuaipeng; Hu, Jingyuan; Dai, Jinyue; Yan, Shifeng; Liu, Xiaoqing
Abstract: Endowing epoxy resin with high performance, controllable degradation as well as feasible upcycling is a huge challenge. Herein, we synthesized a bio‐based amine curing agent containing spiro diacetal unit using an environment‐friendly method, then the controllable degradable epoxy resin was obtained after the curing reaction between diamine (DVPM) and bisphenol A epoxy resin (DGEBA). Results showed that DVPM‐DGEBA resin performed high glass translation temperature of 136°C, glassy storage modulus of 3.93 GPa, and tensile strength of 85.9 MPa, owing to spiro diacetal unit and abundant methoxyl‐related hydrogen bonds confirmed by non‐isothermal fourier transform infrared spectra (FT‐IR) and dynamic mechanical analyses. More importantly, DVPM‐DGEBA resin could decompose into soluble linear oligomers in mild acidic solution. Systematically investigated by 1 H nuclear magnetic resonance, gel permeation chromatography, and FT‐IR. Furthermore, the recycled oligomers could be reprocessed into thermosetting resins in the presence of diamines, and the upcycling resin performed high‐performance (glass translation temperature of 170°C, glassy storage modulus of 6.03 GPa and tensile strength of 86.4 MPa) and flame‐retardant (V‐0 rating). This work gives us some new ideas to achieve the upcycling of the thermoset resin.